A novel method (CCE&C) to study transient phase behaviour in heavy oil and ethane. (1st December 2019) - Modaresghazani, J.; Moore, R.G.; Mehta, S.A.; Anderson, M.; Badamchi-Zadeh, A.
Abstract: Constant Composition Expansion and Compression (CCE&C) experiments, with variable rate of pressure change at iso-thermal conditions, were conducted to investigate the foaming phenomenon on three live-oil samples using a conventional PVT cell. Live-oil samples were prepared in the laboratory by recombining the dead-oil with ethane at different molar fractions of 55, 35 and 15 percent. Recombined live-oil samples were subjected to pressure depletion at different speeds. Three different depletion rates were applied on each live-oil sample at two temperatures of 15 and 75 °C. Each depletion test started at a pressure well above the expected bubble point of the mixture. During the variable rate CCE& C tests, the pressure, total mass and volume of the mixture were recorded. The system was visually monitored for any retrograde swelling (foaming) during depletion or shrinkage (de-foaming) during dissolution. Furthermore, constant composition heating (CCH) tests at isobaric conditions were performed to study the effect of sharp temperature change on foaming behaviour at different compositions of ethane in live-oil. Foaming was observed while doing the pressure depletion test at the fastest speed applied on all the recombined live-oil mixtures at both investigated temperatures. The foaming was more pronounced for 55% live-oil mixture which contained the highest amount of solution gas compared to the next two mixtures. All mixtures showed stronger foaming behavior at 15 °C compared to 75 °C which indicates the foaming phenomenon is more pronounced at lower temperatures. Each pressure depletion test was followed by a compression test at the same speed. A hysteresis was observed in pressure versus total volume for all live-oil samples between the path followed by the mixture during the expansion/compression process.